Zinc Oxide Nanoparticles (ZnONPs) Supplementation in Semen Extender Improves Post-Thaw Quality and Antioxidant Capacity of Gir Bull Spermatozoa - Ram, Dilip R; Parikh, Suryakant S; Panodara, Ramesh J; Chaudhary, Jignesh K; Vala, Karsan B; Solanki, Jayesh Z; Vadher, Dhruv V (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A study was conducted on the semen of four Gir bulls over a six-month period to evaluate the impact of different concentrations of Zinc Oxide Nanoparticles incorporated into the Andromed extender on sperm quality and oxidative stress parameters of cryopreserved semen. A total of 16 semen ejaculates (4 ejaculates per bull) with initial motility more than 70% were used. Semen was extended in Andromed extender @ 80 million sperm per mL, divided into four equal aliquots, and then 1 mg/mL stock solution of ZnONPs was appropriately added to achieve final concentrations of 0.0, 0.5, 1.0, and 1.5 µg/mL. The diluted semen was filled into 0.5 mL French Medium straws, sealed, equilibrated at 4°C for 4 h, and frozen in liquid nitrogen vapour using a conventional wide-mouth freezer. Thawing was done next day in a water bath at 37°C for 30 sec, and various sperm quality parameters and oxidative markers were assessed. Results showed that post-thaw sperm motility, viability, HOST reactive sperm, and acrosomal integrity were significantly (p<0.05) higher at the 1.0 µg/mL ZnONPs concentration (61.31±0.35%, 74.00±0.39%, 64.68±0.29%, and 80.68±0.31%, respectively), while sperm abnormality (14.19±0.19%) was significantly (p<0.05) lower compared to the control, 1.5 µg/mL, and 0.5 µg/mL ZnONPs groups. Additionally, the mean malondialdehyde (MDA) level in post-thaw seminal plasma was lower (1.70±0.10 µM/L, p<0.05) and total antioxidant activity was higher (321.19±9.15 μmol/L, p<0.05) at the 1.0 µg/mL ZnONPs concentration compared to the control, 0.5 µg/mL, and 1.5 µg/mL ZnONPs groups. The study suggests that the addition of 1.0 µg/mL ZnONPs to the semen extender enhances the post-thaw sperm quality and antioxidant capacity of cryopreserved Gir bull semen.